1993
DOI: 10.1136/gut.34.10.1357
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of macrophages and granulocytes expressing L1 protein (calprotectin) in human Peyer's patches compared with normal ileal lamina propria and mesenteric lymph nodes.

Abstract: Antibodies to the cytosolic leucocyte LI protein (or calprotectin) were examined for reactivity with macrophages, neutrophils, and eosinophils identified by paired immunofluorescence staining in sections of normal human ileal mucosa, including Peyer's patches. Macrophages were recognised by expression of the myelomonocytic antigen CD68

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 27 publications
1
72
0
4
Order By: Relevance
“…However, the presence of macrophages, as demonstrated by previous studies [8,46,113], as well as of cells with dendritic morphology described in several species [79,101], are suggestive of primary responses. LP macrophages bear markers associated with cell activation and may play more of a role in antigen presentation than macrophages in the PP [48,49].…”
Section: Lamina Propriasupporting
confidence: 52%
“…However, the presence of macrophages, as demonstrated by previous studies [8,46,113], as well as of cells with dendritic morphology described in several species [79,101], are suggestive of primary responses. LP macrophages bear markers associated with cell activation and may play more of a role in antigen presentation than macrophages in the PP [48,49].…”
Section: Lamina Propriasupporting
confidence: 52%
“…Others [63] have demonstrated that eosinophilic granulocytes are the main cellular source of calprotectin in the normal gut mucosa. However, relatively high levels of calprotectin are found in the stools of normal individualsabout six times the plasma levels (which are about 0.…”
Section: Faecal Calprotectinmentioning
confidence: 99%
“…More than 60% of the total cytosolic protein content of neutrophils is calprotectin. This calcium-and zinc-binding protein plays a regulatory role in inflammation with antimicrobial and antiproliferative properties (12). Fecal calprotectin levels correlate with fecal excretion of neutrophils (13).…”
mentioning
confidence: 99%